Fiscal Devaluation and Fiscal Consolidation : The VAT in Troubled Times - Keen, Michael (IMF Working Papers; Working Paper, 2012)
This paper focuses on two core tax design issues that arise in addressing current fiscal challenges. It first explores the idea, prominent in troubled Eurozone countries, of a "fiscal devaluation": shifting from social contributions to the VAT as a way to mimic a nominal devaluation. Empirical evidence is presented which suggests that in Eurozone countries this may indeed improve the trade balance in the short-run, though, as theory predicts, the effects eventually disappear. The paper then assesses the wider scope for VAT reform in meeting fiscal consolidation needs, developing and beginning to apply a methodology for finding additional VAT revenue in ways less distortionary and fairer than further raising the standard rate.